2008
DOI: 10.1016/j.cell.2008.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Vb Mobilizes Recycling Endosomes and AMPA Receptors for Postsynaptic Plasticity

Abstract: Summary Learning-related plasticity at excitatory synapses in the mammalian brain requires the trafficking of AMPA receptors and the growth of dendritic spines. However, the mechanisms that couple plasticity stimuli to the trafficking of postsynaptic cargo are poorly understood. Here we demonstrate that myosin Vb (MyoVb), a Ca2+-sensitive motor, conducts spine trafficking during long-term potentiation (LTP) of synaptic strength. Upon activation of NMDA receptors and corresponding Ca2+ influx, MyoVb associates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
478
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(504 citation statements)
references
References 48 publications
24
478
2
Order By: Relevance
“…Along similar lines, mislocalization of apical peptidases and transporters to microvillus inclusions and lysosomes has also been observed in enterocytes of Rab8 deficient mice, mimicking the human MVID phenotype [Sato et al, 2007]. In this context, the diagnostic immunoreactivity of intracellular CD10, a membrane-associated neutral peptidase, in MVID enterocytes [Groisman et al, 2002] could be explained by disturbed apical membrane traffic in MVID [Wang et al, 2008]. The three members of the myosin V protein family are differentially expressed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Along similar lines, mislocalization of apical peptidases and transporters to microvillus inclusions and lysosomes has also been observed in enterocytes of Rab8 deficient mice, mimicking the human MVID phenotype [Sato et al, 2007]. In this context, the diagnostic immunoreactivity of intracellular CD10, a membrane-associated neutral peptidase, in MVID enterocytes [Groisman et al, 2002] could be explained by disturbed apical membrane traffic in MVID [Wang et al, 2008]. The three members of the myosin V protein family are differentially expressed.…”
Section: Discussionmentioning
confidence: 95%
“…However, several in vitro studies have shown that myosin Vb facilitates protein recycling in several polarized and nonpolarized cell models by Rab11-dependent mechanisms [Lapierre et al, 2001;Volpicelli et al, 2002;Wakabayashi et al, 2005]. More specifically it has been shown recently that Ca 21 influx at dendritic spines induces a conformational change of myosin Vb and thereby enables recycling of endosomes containing AMPA receptors that are actively translocated along actin filaments to the plasma membrane in vitro [Wang et al, 2008]. The morphology of the PAS-positive tubulovesicular structures in CaCo-2 cells after MYO5B knockdown resembles that of tubular recycling endosomes [Hopkins et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…This delayed dendritic exocytosis could escape our detection with TBOA because they are likely further away from the synapse than perisynaptic AMPARs and hence beyond the reach by spilled synaptic glutamate. On the other hand, we and others have suggested that LTP induction triggers exocytosis of AMPARs, which are subsequently incorporated into synapse and underlie LTP expression (6,(39)(40)(41). Future experiments will be required to resolve this discrepancy.…”
Section: Discussionmentioning
confidence: 97%
“…In mammals and Drosophila, Rab11 and its downstream effectors were shown to interact with myosin V, and this interaction directs the transport of proteins from the recycling endosomes to the apical domain of the plasma membrane in epithelial cells (Hales et al 2002;Cresawn et al 2007;Li et al 2007;Nelson 2009). This conserved myosin-membrane coordination was later shown to be important for the transport of a number of proteins such as cystic fibrosis transmembrane conductance regulator (CFTR) in airway cells and AMPA receptors into spines during synaptic plasticity (Swiatecka-Urban et al 2007;Wang et al 2008;Correia et al 2008). …”
Section: Membrane Organization and Dynamics In Cell Polaritymentioning
confidence: 99%